Identification of critical factors underpinning banks’ lending relationship quality of SMEs: SMEs perspectives / Tury Retap - Retap, Tury (2019)
The Small & Medium-sized Enterprises (SMEs) limited access to banks’ lending has been a global issue owing to asymmetric information problem that have negatively affected SMEs opportunity to borrow. The theory of relationship lending proposes that relationship lending is an effective lending tool to address asymmetric information issue if a bank would lend to the SMEs. The quality of bank-SMEs lending relationships should be strengthened to enhance SMEs access to banks’ lending. Therefore, the key purpose of conducting this research was to identify critical factors underpinning banks’ lending relationship quality of SMEs, to propose a conceptual framework of banks’ lending relationship quality of SMEs and to determine banks’ lending relationship quality composite index of SMEs that would reflect the overall banks’ lending relationship quality of SMEs. A total of 150 survey questionnaire were distributed to the target respondents and 117 responses were successfully collected with a response rate of 62%. The data were captured into SPSS 22 and evaluated by using SMARTPLS 3.2.7 iterative algorithm, bootstrapping and blindfolding procedures to obtain the results. The key findings indicated that long-term relationship orientation, discretionary, commitment and closeness were critical factors underpinning the maintenance and enhancement of banks’ lending relationship quality of SMEs, while trust, satisfaction with the relationship and amount of information sharing have shown trivial effect on banks’ lending relationship quality of SMEs. The overall banks’ lending relationship quality composite index which stood at 4.13 suggested that the SMEs were generally pleased with the quality of lending relationship rendered by their lending banks. The results from assessments in the measurement model and structural model have provided the statistical and empirical evidence that the proposed conceptual framework possessed the quality of explanatory and predictive capability, reliability and validity that would represent a contemporary composite factor model of banks’ lending relationship quality of SMEs which was specific relative to the generic relationship quality model. In order to enhance SMEs access to banks’ lending, lending banks must capitalise on the critical factors identified to strengthen the quality of lending relationship of SMEs. When lending relationship is strong, credit rationing would be reduced when asymmetric information issue is lessened. Hence, the prospect and opportunity of the SMEs access to banks’ lending would be brighter.